A review of Malaysian pesticide laws and regulations / Haidar Dziyauddin...[et al.] - Auddin, Haidar Dziy; Abu Bakar, Syatirah; Abdullah, Mohd Zulhelmey; Manshor, Nurul Mazrah; Roslim, Salmah (2013)
This report presents a critical analysis of the legal and policy issues brought about by the use, management and control of pesticides in Malaysia through a review of the relevant laws and regulations. The use, manufacture, import, sale and storage of pesticides in Malaysia are mainly governed by the Pesticides Act 1974 which objective is to ensure that pesticides sold in the market comply with the standards and specifications at registration. While this main legislation lays down the basic general principles applicable to the use of pesticides, there are still issues and areas for improvement in certain aspects of pesticide regulation and management.